Estetika Muhassinat Lafdziyyah dalam Manuskrip Klasik: Analisis Jinas dan Saja’ pada Mandzumah Al-Mathlab - Muhamad Zidan Alida Putera; Muhammad Alawi Muzhaffar; Lalu Turjiman Ahmad (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2026)
This study aims to deepen the understanding of linguistic beauty and literary values in Mandzumah Al-Mathlab by Sheikh Muntakhab, with a focus on the stylistic devices jinas and saja’ as elements of Arabic rhetoric (balaghah). These rhetorical techniques enrich the aesthetic quality of the text, strengthen moral messages, and highlight the spiritual values present in classical Arabic literature. Using a descriptive qualitative method, the research presents structured explanations based on a verse-by-verse analysis to identify the types and functions of the stylistic elements employed. The findings are arranged in tables to provide clarity and a comprehensive overview of the linguistic features. The results show that 15 verses contain jinas, categorized into five types: jinas mutamatsil, mustaufi, mutharraf, naqis, and mudhari’. Meanwhile, saja’ is found in 37 verses, divided into two types: saja’mutharraf appearing in 33 verses and saja’ mutawazi appearing in 4 verses. Overall, this study distinguishes itself from other analyses of poetic works by highlighting Sheikh Muntakhab's mastery in integrating aesthetic, religious, and moral dimensions within a highly concise frame of 38 verses. He achieves a unique rhetorical equilibrium where jinas and saja' are not merely decorative, but function as structural and cognitive catalysts that accelerate mnemonic internalization for learners.